Conducting consistent laddering interviews using CLAD - Korenini, Bojan (Metodološki zvezki, 2012)
Consistent Laddering is an interviewing technique that is build on top of Laddering technique, which has been used most often in psychotherapy, consumer research, and knowledge acquisition. This paper points out distinctions and advantages of Consistent Laddering over the original technique, as well as some difficulties that concern both techniques. The main purpose of this article is to show how Consistent Laddering interviews are conducted, and how measures employed in this technique are used to detect difficulties that can occur in an interview. Because it is not possible to conduct Consistent Laddering interviews without a computer program, corresponding software, named CLAD, has been developed.
Keywords: Interviews; Intervjuji; Kvalitativna metoda; Qualitative method; Statistical methods; Statistične metode